Method for analyzing high-temperature friction performance of copper crystallizer coating
By performing friction and wear experiments of the copper plate plating layer of the crystal device under high temperature conditions, and combined with the ABAQUS finite element software for simulation analysis, it solves the problem of accurately analyzing the friction and wear behavior of the plating in existing technology. Analyze and optimize the basis for process.
Patent Information
- Application Number
- CN202411483289.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to accurately analyze the friction and wear behavior of the crystallizer copper plate plating under complex vibration modes under high temperature conditions, which affects the service life of the plating and the quality of the steel billet.
Through experimenting on the friction and wear platform of the reciprocating motion of the sine sine mode, the friction coefficient and wear depth of the copper plate plating of the crystal device are measured, and the finite element model is established in ABAQUS software. Analyze the friction and wear behavior of the coating.
A accurate analysis of friction performance under the high temperature conditions of the copper plates of the crystal device, provided the basis for optimizing the production process and improving the performance of the coating, and extended the service life of the plating.
Smart Images

Figure CN119354783A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel continuous casting production, and in particular to a method for analyzing high-temperature friction performance of a copper crystallizer coating. Background Art
[0002] The crystallizer is the "heart" of the continuous casting equipment. During the continuous casting process, the crystallizer forces the molten steel to cool to form a shell with a certain thickness, and ensures that there are no defects such as leakage, deformation, and cracks when it is pulled out of the crystallizer. Due to the billet pulling movement and the vibration of the crystallizer, relative friction will occur between the copper plate of the crystallizer and the billet. Affected by the taper of the crystallizer, the normal load is concentrated on the steel tapping position of the lower mouth of the crystallizer, resulting in particularly serious wear of the coating at the lower mouth of the crystallizer. The coating will gradually consume until the parent material is exposed, causing the copper plate to infiltrate copper to the grain boundary of the billet, thereby causing star cracks in the billet; at the same time, the actual inverted taper of the narrow copper plate will decrease, resulting in a gap between the billet shell and the copper plate, affecting the formation of the billet shell. After the weak billet shell comes out of the crystallizer, it is easy to produce longitudinal cracks at the corners under the action of the static pressure of the molten steel and the mechanical stress. In severe cases, it may cause steel leakage, threatening production safety. Therefore, the quality and life of the crystallizer are directly related to the safe production of steelmaking and the quality of the billet.
[0003] In continuous casting production, the hot surface temperature of the copper plate of the crystallizer can reach 300-400℃. Therefore, high-temperature friction performance is an important indicator for evaluating the quality of the copper plate coating of the crystallizer. During the mutual friction between the coating and the billet shell, complex interactions will occur on the contact surface. When friction and wear occur under high temperature conditions, adhesive wear and plastic deformation are likely to occur between the coating and the billet shell, aggravating the deterioration of friction performance and reducing the service life of the copper plate coating of the crystallizer. There are many factors that affect wear resistance, and the following are generally considered: the normal load on the contact surface; the relative sliding speed between the contact surface and the continuous casting billet; the physical and chemical properties of the material, such as hardness; environmental factors, such as temperature; and the surface roughness of the contact surface.
[0004] At present, a lot of research has been done in the field of friction and wear. Alejandro Sanz et al. (Tribological behavior of coatings for continuous casting of steel. Surface and Coatings Technology, 146–147 (2001) 55–64.) compared the friction and wear behaviors of Ni coating and hard Cr coating through pin-disc experiments in the study of the friction performance of continuous casting crystallizers. The results showed that Ni coatings are softer and prone to plastic deformation, while hard Cr coatings are more brittle and prone to cracking under high temperature and high stress. However, they only conducted qualitative analysis and did not conduct quantitative analysis on the degree of wear of the coatings. Considering that in actual production, the crystallizer usually reciprocates in a sinusoidal or non-sinusoidal mode, it is necessary to further consider and analyze the friction and wear behavior during the reciprocating motion. Patent "CN106918521A" invented a continuous casting mold friction and wear simulation test machine, which controls the temperature of different parts of the molten steel through a heating box and a cooling box, simulating the working environment of the continuous casting mold, and simulating the reciprocating motion of the mold through a crank slider structure, providing a basis for the friction and wear performance analysis of the reciprocating motion of the continuous casting mold in a high temperature environment. However, the crank connecting rod of the device can only achieve a single mode of non-sinusoidal motion, and does not take into account other vibration modes of the mold in actual production. Therefore, there are certain limitations in single experiments, and it is necessary to combine numerical simulation methods to deeply analyze the friction and wear behavior of the mold coating. In the field of mechanical friction, the finite element modeling method based on the ARCHARD wear law has been successfully applied to predict the friction and wear behavior of components. EMBortoleto et al. (Experimental and numerical analysis of dry contact in the pinon disc test [J]. Wear, 2013, 301 (1-2): 19-26.) proposed a calculation method based on the linear ARCHARD wear law and finite element modeling (FEM). The study revealed the phenomenon of unlubricated sliding wear observed in the pin-on-disc test of AISI 4140 pins on the rotating AISI H13 disc. They compared and analyzed the predicted results and experimental results of wear rate and friction coefficient under the conditions of sliding speed of 0.1 m / s and loads of 10, 70 and 140 N, respectively. It was found that the prediction result of mild wear under 10 N was more in line with reality than the prediction of severe wear under 140 N.Patent "CN113705006A" discloses a method for predicting the wear of narrow copper plates in thin slab continuous casting machines. The method establishes a wear model for narrow copper plates during use, calculates the pressure and friction coefficient on the copper plates, substitutes the model into the prediction of the wear of narrow copper plates under different conditions, and modifies the model by comparing it with the actual wear. The method can analyze the influence of different process parameters on wear, but they only modify the wear model from a numerical perspective. Parameters such as friction coefficient and pressure are calculated through empirical formulas, and the influence of the crystallizer vibration mode is not considered.
[0005] In summary, the friction and wear behavior between the copper plate coating of the crystallizer and the blank shell is usually a sinusoidal or non-sinusoidal reciprocating motion under high temperature conditions. At present, there is no more accurate method to determine the wear condition of the coating. Therefore, a suitable method is developed, taking into account the high temperature environment under the actual working conditions of the crystallizer and the reciprocating motion mode between the copper plate coating and the blank shell during the vibration process. The friction and wear data of the sinusoidal mode reciprocating motion are obtained experimentally and applied to the finite element software to calculate the wear of the coating under the corresponding conditions. Subsequently, the experimental data are compared and analyzed with the simulation results to verify the accuracy of the friction and wear model. This method can be used to analyze the high-temperature friction performance of the copper plate coating of the crystallizer, which is of great significance for the real-time evaluation of the service performance and life prediction of the copper plate coating of the crystallizer. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for analyzing the high-temperature friction performance of copper crystallizer coatings in response to the above-mentioned deficiencies in the prior art, and to combine the friction and wear experiment of the crystallizer copper plate coating with simulation to realize the high-temperature friction performance analysis of the crystallizer copper plate coating.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for analyzing the high-temperature friction performance of copper crystallizer coatings, firstly, a friction and wear experiment of the crystallizer copper plate coating is carried out through a friction and wear platform with reciprocating motion in a sinusoidal mode, the friction coefficient of the crystallizer copper plate coating under high temperature conditions is measured, and the wear depth after a certain period of time is obtained; then, a finite element model of the crystallizer coating friction and wear is established in the finite element analysis ABAQUS software, and the friction coefficient measured in the experiment is introduced to perform friction and wear simulation calculations, and the results of the friction and wear experiments and simulation calculations are compared and analyzed to determine the friction and wear behavior of the crystallizer copper plate under complex working conditions, so as to realize the analysis of the high-temperature service performance of the crystallizer copper plate coating. Specifically, the following steps are included:
[0008] Step 1: Prepare a crystallizer copper plate sample and a pin sample for a crystallizer copper plate coating friction and wear test;
[0009] Take a crystallizer copper plate, electroplate the required coating on the crystallizer copper plate, cut the crystallizer copper plate into corresponding sizes according to the friction and wear test platform standard to obtain a crystallizer copper plate sample, and use the crystallizer copper plate sample as the lower sample; use a cylindrical pin sample made of steel material as the upper sample, which is used for friction with the lower sample; clean and dry the crystallizer copper plate sample, weigh the weight of the sample multiple times, and take the average value as the final weight of the crystallizer copper plate sample;
[0010] Step 2: Use the friction and wear experimental platform to conduct a friction and wear experiment on the copper plate coating of the crystallizer to obtain the friction coefficient, wear depth and temperature change under different temperatures, different pressures and different reciprocating frequencies;
[0011] Step 2.1: Assemble the friction and wear test platform, adjust the reciprocating stroke of the crystallizer copper plate sample; place the processed crystallizer copper plate sample into the friction and wear test platform, and install the pin fixture;
[0012] Step 2.2: Heat the temperature of the crystallizer copper plate sample to the predetermined test temperature at the set heating rate until the temperature is stable, and at the same time, the crystallizer copper plate sample reciprocates back and forth to ensure uniform heating of the sample; then, load the corresponding vertical load according to the experimental plan and maintain the set time to stabilize the loading force;
[0013] Step 2.3: Set the corresponding frequency according to the experimental plan, make the pin sample reciprocate on the crystallizer copper plate sample, record the friction coefficient and wear depth of the copper plate coating during the wear process between the pin sample and the crystallizer copper plate sample, the normal and tangential forces and temperature changes of the contact surface between the pin sample and the crystallizer copper plate sample during the friction process; after the experiment, cool the crystallizer copper plate sample to room temperature, weigh its worn weight, and calculate its wear amount; finally, affix a label to the crystallizer copper plate sample to mark the test temperature, frequency and loading force of the crystallizer copper plate sample;
[0014] Step 3: Obtain the wear scar morphology of the coating of the crystallizer copper plate sample after the friction and wear experiment, compare the difference in friction morphology under different conditions, and analyze the influence of temperature and load on the wear behavior;
[0015] Step 4: According to the friction and wear experiment of the crystallizer copper plate coating, a finite element model of the crystallizer coating friction and wear is established. The model establishes the three-dimensional shape of the cylindrical rigid body and the crystallizer copper plate, assigns material properties, sets boundary conditions, and sets the friction and wear behavior calculation method to achieve the stress distribution and wear depth calculation of the crystallizer coating under different friction and wear conditions;
[0016] Step 4.1: According to the sizes of the pin sample and the mold copper plate sample, a cylindrical rigid body and a three-dimensional component of the mold copper plate are established, and the cylindrical rigid body is shelled. The material properties are set based on the actual working conditions, and the material properties are assigned to the friction pair cylindrical rigid body and the three-dimensional component of the mold copper plate, and the two components are assembled together;
[0017] The crystallizer copper plate component includes a crystallizer copper plate substrate and a crystallizer coating, and the crystallizer copper plate substrate and the crystallizer coating are bonded together by using Boolean operation, and the two components are ensured to retain their original material properties;
[0018] Divide the mesh for the cylindrical rigid body component and the three-dimensional copper plate component of the crystallizer, use the hexahedral volume integral unit C3D8, select the mesh and mesh nodes of the contact part between the upper surface of the crystallizer copper plate component and the cylindrical rigid body, and set the ALE adaptive mesh area;
[0019] Step 4.2: Set the bottom of the copper plate component of the crystallizer as a fixed constraint; set a reference point in the cylindrical rigid body component, and bind the cylindrical rigid body to the copper plate component of the crystallizer, constrain the degrees of freedom in the Y and Z directions at the reference point, and apply a load with a direction of (-Z) and a magnitude equal to that of the friction and wear experiment at the reference point;
[0020] Step 4.3: Set the contact mode between the cylindrical rigid body and the copper plate of the crystallizer to surface contact, set the normal behavior of the surface contact attribute to "hard contact", use penalty function constraint, and set the tangential behavior friction coefficient according to the friction and wear test data; set the bottom surface of the cylindrical rigid body as the master surface, and the upper surface of the copper plate of the crystallizer as the slave surface. The nodes contained in the slave surface are the wear nodes in the calculation;
[0021] The tangential behavior friction coefficient is set to the crystallizer coating friction coefficient obtained through the friction and wear test platform, and the crystallizer coating friction coefficient is determined by the friction force between the two surfaces of the pin sample and the crystallizer copper plate sample and the vertical force acting on one surface thereof;
[0022] Step 4.4: Constrain the cylindrical rigid body component through the user subroutine DISP in ABAQUS software, so that it continuously rubs on the surface of the copper plate component of the crystallizer according to the prescribed reciprocating motion rules; calculate the analysis time according to the reciprocating motion cycle and the set number of cycles in the DISP subroutine, and set the analysis step size;
[0023] The prescribed reciprocating motion rule is implemented by using a sinusoidal reciprocating motion control equation;
[0024] Step 4.5: Write the UMESHMONTION subroutine based on the ARCHARD wear formula, call the UMESHMOTION subroutine, update the coordinates of the mesh nodes of the contact part between the upper surface of the copper plate component of the crystallizer and the cylindrical rigid body component involved in the wear simulation, and complete the construction of the crystallizer coating friction and wear finite element model;
[0025] When the wear simulation is performed in ABAQUS finite element software, the wear behavior is described by moving the contact nodes. The UMESHMONTION subroutine accesses the contact point information and records the node contact pressure, node relative sliding displacement and node coordinate data according to the solved crystallizer coating friction and wear finite element model, and then calculates the wear depth and direction according to the ARCHRAD wear formula;
[0026] Step 5: Based on the mold coating friction and wear finite element model, calculate the wear depth of the mold coating under different conditions;
[0027] Step 5.1: Obtain the contact pressure P and sliding distance c of the wear node;
[0028] Step 5.2: Calculate the wear depth of the mold coating; according to the contact pressure and relative slip distance of each time step node, further calculate the contact stress and relative slip velocity to obtain the wear depth dh in the sub-time step, that is, the displacement of the node in the time step;
[0029] Step 5.3: Transfer the calculation results of the UMESHMONTION subroutine to the ABAQUS main program to obtain the simulation result file;
[0030] The simulation result file includes the stress and strain distribution of nodes at each time step in the three-dimensional finite element model of mold coating friction and wear, the displacement results of the nodes, the wear depth and a visual cloud map file for viewing deformation;
[0031] Step 6: Compare and analyze the simulation results obtained in step 5 with the experimental results obtained in step 2. According to the wear amount and wear depth under different friction and wear conditions in the experimental scheme, analyze the high-temperature friction performance of the crystallizer copper plate coating, and determine the accuracy of the simulation model by comparing the degree of agreement between the wear depth curve fitted by the experiment and the wear depth curve extracted by the simulation results.
[0032] The beneficial effect of adopting the above technical solution is that: the present invention provides a method for analyzing the high-temperature friction performance of copper crystallizer coatings, which obtains the friction parameters and wear amount of the crystallizer copper plate coating by conducting friction and wear experiments under different temperatures, different pressures, and different strokes, imports the friction parameters under different conditions into the simulation model for calculation, obtains a relatively accurate simulation result close to the actual working condition, and compares and verifies the simulation result with the experimental result to prove the accuracy of the simulation model. The method of the present invention can realize a relatively accurate analysis of the friction performance of the crystallizer copper plate coating under high temperature conditions, and provides a basis for optimizing the crystallizer copper plate coating manufacturing process and improving the coating performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A flow chart of a method for analyzing high temperature friction performance of a copper crystallizer coating provided by an embodiment of the present invention;
[0034] Figure 2 A schematic diagram of the working principle of the friction and wear experimental platform provided in an embodiment of the present invention;
[0035] Figure 3 A comparison diagram of the copper plate sample of the crystallizer provided in the embodiment of the present invention before and after the friction and wear experiment;
[0036] Figure 4 A schematic diagram of a finite element model of friction and wear of a crystallizer coating provided in an embodiment of the present invention;
[0037] Figure 5 A wear displacement distribution cloud diagram of the crystallizer coating provided in an embodiment of the present invention;
[0038] Figure 6 A wear displacement curve diagram of the mold coating provided in an embodiment of the present invention;
[0039] Figure 7 This is a wear profile curve diagram of the crystallizer coating provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0040] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0041] In this embodiment, a method for analyzing the high-temperature friction performance of a copper crystallizer coating is provided. First, a friction and wear experiment of the crystallizer copper plate coating is carried out through a friction and wear platform that reciprocates in a sinusoidal mode, and the friction coefficient of the crystallizer copper plate coating under high temperature conditions is measured to obtain the wear depth after a certain period of time. Then, a friction and wear finite element model of the crystallizer coating is established in ABAQUS software, and the friction coefficient measured in the experiment is introduced to perform friction and wear simulation calculations. The results of the friction and wear experiment and the simulation calculations are compared and analyzed to determine the friction and wear behavior of the crystallizer copper plate under complex working conditions, thereby realizing the analysis of the high-temperature service performance of the crystallizer copper plate coating. Figure 1 As shown, the specific steps include:
[0042] Step 1: Prepare a crystallizer copper plate sample and a pin sample for a crystallizer copper plate coating friction and wear test;
[0043] Take a crystallizer copper plate, electroplate the required coating on the crystallizer copper plate, cut the crystallizer copper plate into corresponding sizes according to the friction and wear test platform standard to obtain a crystallizer copper plate sample, and use the crystallizer copper plate sample as the lower sample; use 45# steel to make a cylindrical pin sample as the upper sample, which is used for friction with the lower sample;
[0044] In this embodiment, four crystallizer copper plates were taken, and electroplating-grade aminosulfonic acid cobalt solution with a Co content of 20% was used as a plating solution, and coatings with thicknesses of 1 mm, 1.5 mm, and 2 mm were respectively plated; 1% Al2O3 particles were added to two groups of plating solutions, and the specific crystallizer copper plate electroplating scheme is shown in Table 1;
[0045] Table 1 Crystallizer copper plate electroplating plan
[0046]
[0047]
[0048] Before the friction and wear test, the coated crystallizer copper plate was first processed into a rectangular sample with a length, width and height of 35.56mm×25.40mm×8.89mm as the crystallizer copper plate sample, and a cylindrical sample with a size of Φ6mm×10mm was made of 45# steel. Secondly, the crystallizer copper plate sample was placed in a beaker containing anhydrous ethanol, ultrasonically cleaned for 3 to 5 minutes, and finally dried with a hair dryer and dried in a vacuum drying oven. The weight of the sample was weighed three times, and the average value was taken as the final weight of the crystallizer copper plate sample.
[0049] Step 2: Use the friction and wear experimental platform to conduct the friction and wear experiment of the crystallizer copper plate coating, such as Figure 2 As shown, the friction coefficient, wear depth and temperature changes at different temperatures, different pressures and different reciprocating frequencies are obtained;
[0050] Step 2.1: Assemble the friction and wear test platform, adjust the reciprocating stroke of the crystallizer copper plate sample; place the processed crystallizer copper plate sample into the friction and wear test platform, and install the pin fixture;
[0051] Step 2.2: Heat the temperature of the crystallizer copper plate sample to the predetermined test temperature at a heating rate of 1°C / s until the temperature is stable, and at the same time, the crystallizer copper plate sample is reciprocated to ensure uniform heating of the sample; then, load the corresponding vertical load according to the experimental plan and hold it for 5 seconds to stabilize the loading force;
[0052] In this embodiment, the temperature is heated to 280°C, 300°C and 330°C at a heating rate of 1°C / s until the temperature is stable, and the copper plate sample of the crystallizer is reciprocated to make the sample heated evenly. Then, according to the experimental plan, loads of 27N, 60N and 90N are applied and maintained for 5 seconds to stabilize the loading force.
[0053] Step 2.3: Set the corresponding frequency according to the experimental plan, and make the pin sample reciprocate on the crystallizer copper plate sample. The reciprocating motion lasts for 20 minutes. Record the friction coefficient and the wear depth of the copper plate coating during the wear process of the pin sample and the crystallizer copper plate sample, as well as the normal and tangential forces and temperature changes of the contact surface between the pin sample and the crystallizer copper plate sample during the friction process. After the experiment, cool the crystallizer copper plate sample to room temperature, weigh its worn weight, and calculate its wear amount. Finally, a label is attached to the crystallizer copper plate sample to mark the test temperature, frequency, and loading force of the crystallizer copper plate sample.
[0054] In this embodiment, reciprocating motion is performed at frequencies of 1.58HZ, 2.32HZ and 4.34HZ respectively. The reciprocating motion lasts for 20 minutes, and the friction coefficient, depth and temperature change during the wear process are recorded. After the experiment, the worn weight is weighed after cooling to room temperature, and the wear amount is calculated. Finally, a label is attached to the crystallizer copper plate sample, marking the test temperature, frequency and loading force of the sample. The crystallizer copper plate sample is compared before and after the friction and wear experiment. Figure 3 shown.
[0055] In this embodiment, the friction and wear experimental platform was used to conduct experiments, and the method of controlling a single variable was adopted to obtain the friction coefficient, wear depth and temperature change of the crystallizer copper plate coating at different temperatures, different pressures and different reciprocating frequencies, respectively. One set of experimental parameters is shown in Table 2;
[0056] Table 2 Crystallizer copper plate coating wear test parameters
[0057]
[0058]
[0059] The friction and wear experiment conducted in this embodiment is based on the UMT TriboLab friction and wear experimental platform. This experimental platform adopts multiple signal acquisition channels, among which the "X" direction controls the motion positioning system, with a maximum stroke of 120mm, a resolution of 0.25μm, and a speed of 0.002 to 10mm / s, providing accurate positioning and movement of the upper sample; the "Z" direction motion positioning system provides servo-controlled precision loading, which can be programmed to achieve multiple loading modes such as linear, step, constant, and in-situ wear depth detection. The maximum temperature of this experimental platform can reach 1000℃, and the temperature resolution is 0.1℃. The composite motion module can be customized to generate the expected complex motion through the cooperation of the main and auxiliary drivers. The experimental platform adopts a multifunctional modular design, with two modes of rotation test and reciprocating motion test, among which the reciprocating motion mode can meet the needs of the crystallizer vibration experiment. The force measurement of this experimental platform ranges from micronewton to kilonewton, and the test environment can be increased from room temperature to 1000℃. This experimental platform adopts precise closed-loop control sensors with very high precision, which can produce highly accurate and highly repeatable test data.
[0060] Step 3: Use SEM scanning electron microscopy to obtain the wear scar morphology of the coating on the copper plate sample of the crystallizer after the friction and wear test, compare the difference in friction morphology under different conditions, and analyze the influence of temperature and load on the wear behavior;
[0061] Step 4: According to the friction and wear experiment of the crystallizer copper plate coating, a suitable finite element three-dimensional model of the crystallizer coating friction and wear is established. The model establishes the three-dimensional shape of the friction pair cylindrical rigid body and the crystallizer copper plate, assigns material properties, sets boundary conditions, and sets the friction and wear behavior calculation method to achieve the stress distribution and wear depth calculation of the crystallizer coating under different friction and wear conditions;
[0062] Step 4.1: According to the sizes of the pin sample and the mold copper plate sample, a cylindrical rigid body and a three-dimensional component of the mold copper plate are established, and the cylindrical rigid body is shelled. Appropriate material properties are set based on the actual working conditions, and the material properties are assigned to the friction pair cylindrical rigid body and the three-dimensional component of the mold copper plate, and the two components are assembled together;
[0063] The crystallizer copper plate component includes a crystallizer copper plate substrate and a crystallizer coating. Since the crystallizer copper plate substrate and the crystallizer coating are integrated, a Boolean operation is used to bond the crystallizer copper plate substrate and the crystallizer coating together, and it is ensured that the two components retain their original material properties.
[0064] Divide the grid for the cylindrical rigid body component and the three-dimensional copper plate component of the crystallizer, use the hexahedral volume integral unit C3D8, select the grid and grid nodes of the contact part between the upper surface of the crystallizer copper plate component and the cylindrical rigid body, and set the ALE (Arbitrary Lagrangian-Eulerian or Arbitrary Lagrangian-Eulerian method) adaptive grid area;
[0065] In this embodiment, the relevant parameters of the friction pair cylindrical rigid body and the crystallizer copper plate are established as follows: the friction pair is a cylindrical rigid body with a diameter of 6mm and a height of 10mm, the length, width and height of the crystallizer copper plate are 35.56mm, 25.4mm and 8.89mm respectively, and the length, width and height of the crystallizer coating are 35.56mm, 25.4mm and 1.0mm respectively. The vibration stroke is 12mm, the frequency is 15.7min-1, and its physical properties are shown in Table 3; after assembly, set appropriate boundary conditions and divide the grid.
[0066] Table 3 Physical properties of the crystallizer copper plate and its coating
[0067]
[0068]
[0069] In this embodiment, the friction pair cylindrical rigid body and the crystallizer copper plate component are established based on the finite element software ABAQUS. Since the hardness of the cylindrical rigid body is much greater than the measured surface hardness of the crystallizer copper plate component, the cylindrical rigid body is modeled using a discrete rigid body to improve the calculation speed. Appropriate material properties are set based on the actual working conditions, and the two components are assembled together. The crystallizer copper plate component is divided into two parts, of which the part in contact with the cylindrical rigid body is the ALE adaptive mesh area. The material of the crystallizer copper plate component uses the elastic-plastic modeling method, and the parameters are set according to the mechanical properties of the coating material.
[0070] The cylindrical rigid body and the three-dimensional copper plate of the crystallizer use the hexahedral volume integral unit C3D8, which includes 80784 hexahedral units. There are 87308 nodes in total, of which 475 are the contact surface nodes of the cylindrical rigid body and the crystallizer copper plate. The three-dimensional finite element model of the friction and wear of the crystallizer coating is as follows: Figure 4 In order to ensure the rationality of the subdivision, this embodiment adopts a custom subdivision, which ensures that the subdivision nodes of the friction pair cylindrical rigid body contact surface and the subdivision nodes of part of the crystallizer copper plate contact surface are at the same position, which is convenient for friction and wear simulation. At the same time, the mesh at the crystallizer copper plate contact surface is divided into finer ones to make the results of wear simulation more accurate.
[0071] Step 4.2: In the actual friction and wear experiment, the bottom of the crystallizer copper plate sample is fixed, so in the finite element simulation, the bottom of the crystallizer copper plate component needs to be set as a fixed constraint; a reference point is set in the cylindrical rigid body component, and the cylindrical rigid body is bound to the crystallizer copper plate component, the degrees of freedom in the Y and Z directions are constrained at the reference point, and a load with a direction (-Z) and a magnitude equal to that in the friction and wear experiment is applied at the reference point; in this embodiment, a load with a direction (-Z) and a magnitude of 30N, which is equal to the actual load in the friction and wear experiment, is applied at the reference point.
[0072] Step 4.3: Set the contact mode between the cylindrical rigid body and the copper plate of the crystallizer to surface contact, set the normal behavior of the surface contact attribute to "hard contact", use penalty function constraint, and set the tangential behavior friction coefficient according to the friction and wear test data; set the bottom surface of the cylindrical rigid body as the master surface, and the upper surface of the copper plate of the crystallizer as the slave surface. The nodes contained in the slave surface are the wear nodes in the calculation;
[0073] The tangential behavior friction coefficient is set to the crystallizer coating friction coefficient obtained through the friction and wear experimental platform. The crystallizer coating friction coefficient is determined by the friction force between the two surfaces of the pin sample and the crystallizer copper plate sample and the vertical force acting on one surface thereof. By setting different experimental parameters, the experimental environment identical to the actual working conditions can be simulated, and the obtained friction coefficient is closer to the actual situation.
[0074] In this embodiment, the tangential behavior friction coefficient is set to 0.5; Step 4.4: constrain the cylindrical rigid body component through the user subroutine DISP in the ABAQUS software, so that it continuously rubs on the surface of the crystallizer copper plate component according to the prescribed reciprocating motion rule; calculate the analysis time according to the reciprocating motion cycle and the set number of cycles in the DISP subroutine, and set a reasonable analysis step size;
[0075] In this embodiment, the prescribed reciprocating motion rule is implemented using a sinusoidal reciprocating motion control equation, as shown in the following formula:
[0076]
[0077] Where, s is the displacement of the cylindrical rigid body, mm; h is the vibration stroke (twice the amplitude), mm; f is the vibration frequency, min -1 ; t is time, s.
[0078] Step 4.5: Write the UMESHMONTION subroutine based on the ARCHARD wear formula, call the UMESHMOTION subroutine, update the coordinates of the mesh nodes of the contact part between the upper surface of the copper plate component of the crystallizer and the cylindrical rigid body component involved in the wear simulation, and complete the construction of the finite element three-dimensional model of the crystallizer coating friction and wear;
[0079] When the wear simulation is performed in ABAQUS finite element software, the wear behavior is described by moving the contact nodes. The UMESHMONTION subroutine accesses the contact point information and records the node contact pressure, node relative sliding displacement and node coordinate data based on the solved crystallizer coating friction and wear finite element three-dimensional model, and then calculates the wear depth and direction according to the ARCHRAD wear formula;
[0080] The ARCHARD wear formula is as follows:
[0081]
[0082] Dividing equation (2) by the surface wear area A, we can get the following equation:
[0083]
[0084] Among them, V is the wear amount, unit is g; A is the surface wear area, unit is mm; c is the sliding distance, mm; K is the Archard wear coefficient; F is the normal force applied to the upper specimen, unit is N; H is the material hardness, unit is HV.
[0085] Since the wear depth h is more convenient to express than the wear volume, the wear depth is defined as h = V / A, and the contact pressure is P = F / A. Then the expression of the wear depth is as follows:
[0086]
[0087] Step 5: Based on the mold coating friction and wear finite element three-dimensional model, calculate the wear depth of the mold coating under different conditions;
[0088] Step 5.1: Obtain the contact pressure P and sliding distance c of the wear node;
[0089] Step 5.2: Calculate the wear depth of the mold coating; according to the contact pressure and relative slip distance of each time step node, further calculate the contact stress and relative slip velocity to obtain the wear depth dh in the sub-time step, that is, the displacement of the node in the time step;
[0090] The finite element calculation formula of Archard wear formula is:
[0091]
[0092] Where dh is the wear depth, mm; K is the Archard wear coefficient; v is the relative slip velocity, mm / s; dt is the sliding time, s; A is the contact area, mm 2 ; P is the contact pressure, MPa.
[0093] Step 5.3: Transfer the calculation results of the UMESHMONTION subroutine to the ABAQUS main program to obtain the simulation result file;
[0094] The simulation result file includes the stress and strain distribution of nodes at each time step in the three-dimensional finite element model of mold coating friction and wear, the displacement results of the nodes, the wear depth and a visual cloud map file for viewing deformation;
[0095] In this embodiment, the wear displacement distribution of the mold coating, the wear displacement curve of the mold coating and the wear profile curve of the mold coating are respectively as follows: Figure 5-Figure 7 shown.
[0096] Step 6: Compare and analyze the simulation results obtained in step 5 with the experimental results obtained in step 2. According to the wear amount and wear depth under different friction and wear conditions in the experimental scheme, analyze the high-temperature friction performance of the crystallizer copper plate coating, and determine the accuracy of the simulation model by comparing the degree of agreement between the wear depth curve fitted by the experiment and the wear depth curve extracted by the simulation results.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope defined by the claims of the present invention.
Claims
1. A method for analyzing high temperature friction performance of copper crystallizer coating, characterized in that: Firstly, the friction and wear experiment of the crystallizer copper plate coating was carried out through a friction and wear platform with sinusoidal reciprocating motion, and the friction coefficient of the crystallizer copper plate coating under high temperature conditions was measured, and the wear depth after a certain period of time was obtained; then, a finite element model of the crystallizer coating friction and wear was established in the finite element analysis software ABAQUS, and the friction coefficient measured in the experiment was introduced for friction and wear simulation calculation. The results of the friction and wear experiment and the simulation calculation were compared and analyzed, and the friction and wear behavior of the crystallizer copper plate under complex working conditions was determined, so as to realize the analysis of the high temperature service performance of the crystallizer copper plate coating.
2. A method for analyzing high temperature friction performance of a copper crystallizer coating according to claim 1, characterized in that: The following steps are involved: Step 1: Prepare a crystallizer copper plate sample and a pin sample for a crystallizer copper plate coating friction and wear test; Step 2: Use the friction and wear experimental platform to conduct a friction and wear experiment on the copper plate coating of the crystallizer to obtain the friction coefficient, wear depth and temperature change under different temperatures, different pressures and different reciprocating frequencies; Step 3: Obtain the wear scar morphology of the coating of the crystallizer copper plate sample after the friction and wear experiment, compare the difference in friction morphology under different conditions, and analyze the influence of temperature and load on the wear behavior; Step 4: According to the friction and wear experiment of the crystallizer copper plate coating, a finite element model of the crystallizer coating friction and wear is established. The model establishes the three-dimensional shape of the cylindrical rigid body and the crystallizer copper plate, assigns material properties, sets boundary conditions, and sets the friction and wear behavior calculation method to achieve the stress distribution and wear depth calculation of the crystallizer coating under different friction and wear conditions; Step 5: Based on the mold coating friction and wear finite element model, calculate the wear depth of the mold coating under different conditions and the simulation result file; Step 6: Compare and analyze the simulation results obtained in step 5 with the experimental results obtained in step 2. According to the wear amount and wear depth under different friction and wear conditions in the experimental scheme, analyze the high-temperature friction performance of the crystallizer copper plate coating, and determine the accuracy of the simulation model by comparing the degree of agreement between the wear depth curve fitted by the experiment and the wear depth curve extracted by the simulation results.
3. A method for analyzing high temperature friction performance of a copper crystallizer coating according to claim 2, characterized in that: The specific method of step 1 is: Take a crystallizer copper plate, electroplate the required coating on the crystallizer copper plate, cut the crystallizer copper plate into corresponding sizes according to the friction and wear experimental platform standard to obtain a crystallizer copper plate sample, and use the crystallizer copper plate sample as the lower sample; use steel material to make a cylindrical pin sample as the upper sample, which is used for friction with the lower sample; clean and dry the crystallizer copper plate sample, weigh the weight of the sample multiple times, and take the average value as the final weight of the crystallizer copper plate sample.
4. A method for analyzing high temperature friction performance of a copper mold coating according to claim 2, characterized in that: The specific method of step 2 is: Step 2.1: Assemble the friction and wear test platform, adjust the reciprocating stroke of the crystallizer copper plate sample; place the processed crystallizer copper plate sample into the friction and wear test platform, and install the pin fixture; Step 2.2: Heat the temperature of the crystallizer copper plate sample to the predetermined test temperature at the set heating rate until the temperature is stable, and at the same time, the crystallizer copper plate sample reciprocates back and forth to ensure uniform heating of the sample; then, load the corresponding vertical load according to the experimental plan and maintain the set time to stabilize the loading force; Step 2.3: Set the corresponding frequency according to the experimental plan to make the pin sample reciprocate on the crystallizer copper plate sample, record the friction coefficient between the pin sample and the crystallizer copper plate sample, the wear depth of the copper plate coating, the normal and tangential forces and temperature changes of the contact surface between the pin sample and the crystallizer copper plate sample during the friction process; after the experiment, cool the crystallizer copper plate sample to room temperature, weigh its weight after wear, and calculate its wear amount; finally, a label is attached to the crystallizer copper plate sample to mark the test temperature, frequency and loading force of the crystallizer copper plate sample.
5. A method for analyzing high temperature friction performance of copper crystallizer coating according to claim 4, characterized in that: The specific method of step 4 is: Step 4.1: According to the sizes of the pin sample and the mold copper plate sample, a cylindrical rigid body and a three-dimensional component of the mold copper plate are established, and the cylindrical rigid body is shelled. The material properties are set based on the actual working conditions, and the material properties are assigned to the friction pair cylindrical rigid body and the three-dimensional component of the mold copper plate, and the two components are assembled together; Divide the mesh for the cylindrical rigid body component and the three-dimensional copper plate component of the crystallizer, use the hexahedral volume integral unit C3D8, select the mesh and mesh nodes of the contact part between the upper surface of the crystallizer copper plate component and the cylindrical rigid body, and set the ALE adaptive mesh area; Step 4.2: Set the bottom of the copper plate component of the crystallizer as a fixed constraint; set a reference point in the cylindrical rigid body component, and bind the cylindrical rigid body to the copper plate component of the crystallizer, constrain the degrees of freedom in the Y and Z directions at the reference point, and apply a load with a direction of (-Z) and a magnitude equal to that of the friction and wear experiment at the reference point; Step 4.3: Set the contact mode between the cylindrical rigid body and the copper plate of the crystallizer to surface contact, set the normal behavior of the surface-to-surface contact attribute to "hard contact", adopt the penalty function constraint, and set the tangential behavior friction coefficient according to the friction and wear test data; set the bottom surface of the cylindrical rigid body as the master surface, and the upper surface of the copper plate of the crystallizer as the slave surface. The nodes contained in the slave surface are the wear nodes in the calculation; Step 4.4: Constrain the cylindrical rigid body component through the user subroutine DISP in ABAQUS software, so that it continuously rubs on the surface of the copper plate component of the crystallizer according to the prescribed reciprocating motion rules; calculate the analysis time according to the reciprocating motion cycle and the set number of cycles in the DISP subroutine, and set the analysis step size; Step 4.5: Write the UMESHMONTION subroutine based on the ARCHARD wear formula, call the UMESHMOTION subroutine, update the coordinates of the mesh nodes of the contact part between the upper surface of the copper plate component of the crystallizer and the cylindrical rigid body component involved in the wear simulation, and complete the construction of the crystallizer coating friction and wear finite element model; When the wear simulation is performed in ABAQUS finite element software, the wear behavior is described by moving the contact nodes. The UMESHMONTION subroutine accesses the contact point information and records the node contact pressure, node relative sliding displacement and node coordinate data according to the solved crystallizer coating friction and wear finite element model, and then calculates the wear depth and direction according to the ARCHRAD wear formula.
6. A method for analyzing high temperature friction performance of copper crystallizer coating according to claim 5, characterized in that: The crystallizer copper plate component described in step 4.1 includes a crystallizer copper plate substrate and a crystallizer coating. The crystallizer copper plate substrate and the crystallizer coating are bonded together using Boolean operations, and the two components are ensured to retain their original material properties.
7. A method for analyzing high temperature friction performance of a copper mold coating according to claim 5, characterized in that: The tangential behavior friction coefficient described in step 4.3 is set to the crystallizer coating friction coefficient obtained through the friction and wear experimental platform. The crystallizer coating friction coefficient is determined by the friction force between the two surfaces of the pin sample and the crystallizer copper plate sample and the vertical force acting on one surface thereof.
8. The method for analyzing high temperature friction performance of a copper mold coating according to claim 5, characterized in that: The reciprocating motion rule specified in step 4.4 is implemented using the sinusoidal reciprocating motion control equation.
9. A method for analyzing high temperature friction performance of a copper mold coating according to claim 5, characterized in that: The specific method of step 5 is: Step 5.1: Obtain the contact pressure P and sliding distance c of the wear node; Step 5.2: Calculate the wear depth of the mold coating; according to the contact pressure and relative slip distance of each time step node, further calculate the contact stress and relative slip velocity to obtain the wear depth dh in the sub-time step, that is, the displacement of the node in the time step; Step 5.3: Transfer the calculation results of the UMESHMONTION subroutine to the ABAQUS main program to obtain the simulation result file; The simulation result file includes the stress and strain distribution of nodes at each time step in the three-dimensional finite element model of crystallizer coating friction and wear, the displacement results of the nodes, the wear depth and a visualization cloud map file for conveniently viewing the deformation.
Citation Information
Patent Citations
Friction wear simulation experiment machine of continuous casting crystallizer
CN106918521A
Method for predicting abrasion of narrow-face copper plate of thin slab continuous casting machine
CN113705006A
Cited By
Method and device for evaluating sealing performance of sealing structure
CN120597588A
Method for measuring wear coefficient and predicting service life of carburizing material at different positions
CN122631471A